2005
DOI: 10.1136/gut.2005.072009
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow up of patients treated for Helicobacter pylori infection

Abstract: Background: Helicobacter pylori infection induces progressive inflammatory changes in the gastric mucosa that may lead to gastric cancer. Understanding long term effects resulting from the cure of this infection is needed to design cancer prevention strategies. Methods: A cohort of 795 adults with preneoplastic gastric lesions was randomised to receive anti-H pylori treatment and/or antioxidants. At the end of six years of intervention, those who did not receive anti-H pylori treatment were offered it. Gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
282
1
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(308 citation statements)
references
References 28 publications
15
282
1
10
Order By: Relevance
“…The formation of this dimer was dependent on ERK phosphorylation and resulted in c-Myc and ODC expression and apoptosis. These findings are important because failure of the immune response to H. pylori contributes to its strong ability to colonize, as evidenced by prevalence rates approaching 100% in underdeveloped regions (45). Our work provides new insight into the molecular mechanism underlying the polyamine-mediated macrophage apoptosis that contributes to the immunopathogenesis of H. pylori infection.…”
Section: Discussionmentioning
confidence: 88%
“…The formation of this dimer was dependent on ERK phosphorylation and resulted in c-Myc and ODC expression and apoptosis. These findings are important because failure of the immune response to H. pylori contributes to its strong ability to colonize, as evidenced by prevalence rates approaching 100% in underdeveloped regions (45). Our work provides new insight into the molecular mechanism underlying the polyamine-mediated macrophage apoptosis that contributes to the immunopathogenesis of H. pylori infection.…”
Section: Discussionmentioning
confidence: 88%
“…China have demonstrated a beneficial effect of eradicating the bacteria even in patients with precancerous conditions (34,120,139) . Even though the further advanced the existing preneoplastic condition is, the less likely it is that H pylori eradication will stop gastric cancer development (37,59) , a randomized study of patients undergoing H pylori eradication following early gastric cancer resection was able to demonstrate a reduction in the appearance of metachronous gastric cancer (66) .…”
Section: Randomized Controlled Trials Conducted In Colombia Andmentioning
confidence: 99%
“…Intervention studies conducted in Latin America and Asia and meta-analysis have shown that H pylori eradication is an effective step in preventing gastric cancer, particularly if treatment is performed on patients prior to development of precancerous conditions (atrophic gastritis and intestinal metaplasia) (65,139,193,206,210) . Studies using animal models have also confirmed that gastric cancer development can be prevented by early eradication of the microorganism (14,151) .…”
Section: Statement 17mentioning
confidence: 99%
“…As H pylori infection plays an important role in gastric cancer pathogenesis, the elimination of H pylori has great importance. Evidences point out a significant reduction in the risk of gastric cancer development following H pylori eradication (Mera et al, 2005;Take et al, 2005;Fuccio et al, 2009). More accentuated in wealthy societies, a steady decrease in the prevalence of H pylori infection and the incidence of gastric cancer has been observed in most populations in recent decades (Correa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%